A qualitative exploration of the motor skills required for elite triathlon performance. (September 2022) - Chesher, Stuart M.; Rosalie, Simon M.; Netto, Kevin J.; Charlton, Paula C.; van Rens, Fleur E.C.A.
Abstract: Purpose: The purpose of this research was to investigate the beliefs, attitudes, and experiences of stakeholders in youth triathlon regarding the important motor subskills that are required to be successful at the elite level of triathlon competition. Method: Twenty-five participants were recruited from five stakeholder groups in triathlon and interviewed via video conference. A constructionist and relativist approach to thematic analysis was used to identify three first order themes and several second order themes. Results: The first, first order theme was 'Continuous Motor Skills' which consisted of the invariant features of triathlon's continuous motor skills and the parameterization of continuous motor skills. The second, first order theme was 'Discrete Motor Skills' and consisted of discrete motor skills involved with cornering and change of direction in each discipline and transition phases in triathlon. The final first order theme was 'Adaptability in Continuous and Discrete Motor Skills'. Conclusion: This research provides a novel and more broad understanding of the beliefs, attitudes, and experiences of stakeholders in triathlon regarding important motor skills that are required to succeed at the elite level of the sport. This novel and broad understanding of important triathlon motor skills has theoretical implications for evaluating triathlon performance with skill acquisition as a primary focus. Additionally, this research is practically important for coaches, administrators, and athletic performance staff who design training programs and pathways for young, developing triathletes. Highlights: Participants believe that proficient motor skills are important for elite success. Intentional practise of continuous and discrete motor skills should be programmed. Triathletes motor skill performances are required to be highly adaptable. The theoretical basis for a triathlon skill acquisition framework is provided.